PERLINDUNGAN HUKUM TERHADAP PEKERJA ATAS KESELAMATAN DAN KESEHATAN KERJA - Riyayan, Allan Ardi; Wardani, Susilo (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
The purpose of this study is regarding the implementation of legal protection and efforts to prevent work accidents. The research method used is empirical using a factual approach. The data collection method uses the interview method and literature study. The data analysis method used is qualitative. The results of the study show legal protection for workers for K3 at PT. Geo Dipa Energi Wonosobo, namely (1). economic form of protection. (2). Social protection or occupational health and. (3). Technical protection or work safety. Accident prevention efforts at PT. Geo Dipa Energi Wonosobo, namely by implementing Job Safety Analysis (JSA) by identifying hazards and their control at each stage of work, namely by implementing Job Safety Analysis. The implementation of Job Safety Analysis (JSA) at PT. Geo Dipa Energi Wonosobo can help make it easier for workers to take safe work steps and can avoid various existing hazards.